Amla as an antihyperglycemic and hepato-renal protective agent in fluoride induced toxicity - Rupal A Vasant; A. V. R. L. Narasimhacharya (Wolters Kluwer Medknow Publications, 2012)
Purpose of the study was to examine the antihyperglycemic and hepato-renal protective effects of Emblica officinalis (Eo) fruit as a food supplement in fluoride induced toxicity. Eo fruit powder was incorporated into the diet (2.5, 5 and 10 gm %) of fluoride exposed animals for a duration of 30 days. Fluoride exposure caused significant elevation in plasma glucose, serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvate transaminase (SGPT), acid phosphatase (ACP), alkaline phosphatase (ALP) activities, hepatic glucose-6-phosphatase (G-6-Pase) and decreased hepatic glycogen content, hexokinase activity and antioxidant profiles (hepatic and renal). An inclusion of Eo fruit powder significantly reduced plasma glucose levels, SGOT, SGPT, ACP and ALP activities, hepatic G-6-Pase activity and increased hepatic glycogen content and hexokinase activity. Hepatic and renal antioxidant status of fluoride exposed animals improved upon feeding Eo fruit powder. We, therefore, conclude that E. officinalis fruit could be useful in regulating hyperglycemia and enhances antioxidant status of fluoride exposed animals.